(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The banking industry worldwide has continued to evolve over the past decade due to many factors, including globalization, liberalization of financial markets, changes in banking regulation, and, of course, constant changes in the increasing demand of customers for high-quality banking services. Modern information technologies, especially Blockchain technologies, will fundamentally change the appearance of current financial and banking institutions. For the banking sector, the issue of innovative development and the development of types and mechanisms for ensuring a stable and effective process of creating and implementing Blockchain technologies is very relevant since the inconsistency of their work hinders the effective development of banking activities. In the banking sector, Blockchain technology shows dynamic development and attracts attention. The novelty of this technology lies in the fact that information about transactions is not stored in a centralized database but is transferred to the computers of all network participants, who reserve the data locally. For the banking sector, the issue of innovative development and the development of types and mechanisms for ensuring a stable and effective process of creating and implementing Blockchain technologies is very relevant since the inconsistency of their work hinders the effective development of banking activities.